2008
DOI: 10.1021/es0716554
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Inflammatory Potential of Soot Particles of Low-Emission Diesel Engines

Abstract: We evaluated, in vitro, the inflammatory and cytotoxic potential of soot particles from current low-emission (Euro IV) diesel engines toward human peripheral blood monocyte-derived macrophage cells. The result is surprising. At the same mass concentration, soot particles produced under low-emission conditions exhibit a much highertoxic and inflammatory potential than particles from an old diesel engine operating under black smoke conditions. This effect is assigned to the defective surface structure of Euro IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 12 publications
1
71
0
7
Order By: Relevance
“…According to Su et al, 38 the size of the soot particles emitted from modern Euro IV engines is significantly smaller than those emitted from older engines. Su et al 38 also showed that the soot emitted from new-technology engines have increased cytotoxic effects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Su et al, 38 the size of the soot particles emitted from modern Euro IV engines is significantly smaller than those emitted from older engines. Su et al 38 also showed that the soot emitted from new-technology engines have increased cytotoxic effects.…”
Section: Discussionmentioning
confidence: 97%
“…According to Su et al, 38 the size of the soot particles emitted from modern Euro IV engines is significantly smaller than those emitted from older engines. Su et al 38 also showed that the soot emitted from new-technology engines have increased cytotoxic effects. In this study, the authors have shown that the open channel filters collect nanosized particles with high collection efficiency: the collection efficiency for particles smaller than 20 nm was over 80%.…”
Section: Discussionmentioning
confidence: 97%
“…Harder et al (2005) reported the effect of BC on heart-rate increase but no inflammatory effects, while Cho et al (2005) observed a correlation between ambient soot carbon and PM oxidative potential. Su et al (2008) suggested that soot carbon toxicity depends on soot particle morphology, while the WHO report (2012) concluded that BC particles may not be the harmful component of PM but may act as carrier of a large variety of toxic species, such as organic molecules, which are co-emitted with soot carbon. A simultaneous investigation of soot particle morphology and toxicity is very limited Su et al, 2008) and was performed only with transmission electron microscopy (TEM), which does not give information on soot-carbonorganic-carbon mixing or information on OC composition.…”
Section: Particulate Matter and Healthmentioning
confidence: 99%
“…Particle toxic potential has been associated with serious adverse health effects, including respiratory symptoms impaired lung function and cardiovascular diseases (Geller et al, 2006;Bernstein et al, 2004). It is found that newer diesel engines emit nanoparticles that could be more harmful to human health than older engines because particles with diameters of 5-20 nm may penetrate the lung more deeply (Su et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…InfraRed studies show a high concentration of hydroxyl functional groups on Euro IV soot compared to soot emitted by older engines (Su et al, 2008), and hence an increased hydrophilicity which facilitates interactions with hydrophilic biomolecules (Popovicheva et al, 2009a). Based on inflammatory and cytotoxic responses to in vitro and in vivo particle exposures, the hazardous substances are found on particles emitted by various vehicles but risks associated to chemical forms of these emissions are remaining uncertain (Maier et al, 2008;Muller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%